2003
DOI: 10.1097/01.ju.0000072422.69286.0e
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Patients With Pelvic Lymph Node Metastases Following Radical Cystectomy With En Bloc Pelvic Lymphadenectomy: The Concept of Lymph Node Density

Abstract: Patients with lymph node tumor involvement following radical cystectomy may be stratified into high risk groups based on the primary bladder tumor, pathological subgroup, number of lymph nodes removed and total number of lymph nodes involved. Lymph node density, which is a novel prognostic indicator, may better stratify lymph node positive cases because this concept collectively accounts for the total number of positive lymph nodes (tumor burden) and the total number of lymph nodes removed (extent of lymphaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
309
6
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(343 citation statements)
references
References 14 publications
12
309
6
16
Order By: Relevance
“…Recent studies have emphasized the importance of lymph node density for nodal staging. [100][101][102][103] Lymph node density is defined by the ratio of positive lymph nodes to the total number of lymph nodes sampled. In an analysis of 248 patients with positive nodal metastasis, Kassouf et al 101 found that lymph node density was an independent predictor of cancer survival.…”
Section: Stage Pt4 Carcinomamentioning
confidence: 99%
“…Recent studies have emphasized the importance of lymph node density for nodal staging. [100][101][102][103] Lymph node density is defined by the ratio of positive lymph nodes to the total number of lymph nodes sampled. In an analysis of 248 patients with positive nodal metastasis, Kassouf et al 101 found that lymph node density was an independent predictor of cancer survival.…”
Section: Stage Pt4 Carcinomamentioning
confidence: 99%
“…LND has been demonstrated to be directly correlated with recurrence-free survival [3][4][5][6]. In a recent review, LND was found to be a better surrogate end point than total number of positive nodes in four out of five studies in the literature evaluated by Herr [14].…”
mentioning
confidence: 99%
“…Thus, LND takes two known prognostic factors for recurrence and combines them into one composite variable (a percentage) [4][5][6]. The numerator (number of positive nodes) is one component of the American Joint Committee on Cancer (AJCC) staging criteria and incorporating this variable makes intuitive sense as the greater the extent of disease the worse the prognosis will be.…”
mentioning
confidence: 99%
See 2 more Smart Citations